Psychiatric Rehabilitation: An Overview for Rehabilitation Practitioners - Xiangli CHEN; Deborah LEE (康复学报)
Mental illness seriously interferes with the individual's ability to participate and perform major life activities. Individuals with serious mental illness may have limited capacity to perform certain tasks and functions such as obtaining gainful employment or the ability to fully participate in community activities. Psychiatric rehabilitation addresses both the psychosocial and vocational issues by promoting recovery and improving quality of life in individuals with severe mental illness. The purpose of this paper is to introduce psychosocial barriers faced by individuals with psychiatric disabilities, strategies used in psychiatric rehabilitation and evidence-based practices. Psychosocial barriers include social and self-stigma, unemployment and poverty. Effective rehabilitation strategies include cognitive rehabilitation, skills training, instrumental and social support, and vocational interventions. Five evidence-based interventions that are identified for psychiatric rehabilitation include assertive community treatment (ACT), family psychoeducation (FPE), supported employment (SE), illness management and recovery (IMR) and integrated due disorder treatment (IDDT). Future research should focus on overcoming psychosocial barriers and utilizing evidence-based practice with interdisciplinary team approach for better contribution to society.